1994
DOI: 10.2105/ajph.84.4.618
|View full text |Cite
|
Sign up to set email alerts
|

Aggression and fighting behavior among African-American adolescents: individual and family factors.

Abstract: OBJECTIVES. This study examined the extent to which individual and family factors are associated with aggression and fighting behavior among African-American middle school adolescents. METHODS. Four hundred thirty-six African-American boys and girls from two middle schools in a predominantly low-income North Carolina school system were surveyed and their school records examined. Information was collected concerning students' aggression levels, school fighting behavior, school suspensions for fighting, attitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0
3

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(59 citation statements)
references
References 5 publications
6
50
0
3
Order By: Relevance
“…These results suggested stronger program effects on some outcome variables for boys compared to girls, and for middle school students compared to elementary school students. Because males and older youth tend to engage in more serious aggression than girls and younger children (e.g., Cotton et al, 1994;Federal Bureau of Investigation, 1991;Shapiro, Dorman, Welker, & Clough, 1998), these results suggest stronger program effects for students needing these benefits the most.…”
Section: Discussionmentioning
confidence: 93%
“…These results suggested stronger program effects on some outcome variables for boys compared to girls, and for middle school students compared to elementary school students. Because males and older youth tend to engage in more serious aggression than girls and younger children (e.g., Cotton et al, 1994;Federal Bureau of Investigation, 1991;Shapiro, Dorman, Welker, & Clough, 1998), these results suggest stronger program effects for students needing these benefits the most.…”
Section: Discussionmentioning
confidence: 93%
“…[1][2][3][4][5][6][7][8][9][10][11][12] We expect schools to provide a safe environment so that effective learning can take place; however, the prevalence of violence in schools is increasing. 7,[13][14][15][16][17][18][19] The Centers for Disease Control and Prevention reported that in 1993, 11.8% of high school students had recently carried a weapon to school and 16.2% had been in a fight at school. 20 DuRant et al 7 found that 15% of male students and 5% of female students in grades 9 through 12 in Massachusetts had carried a weapon, including guns, knives, or clubs, to school in the 30 days prior to the survey.…”
Section: ])mentioning
confidence: 99%
“…Researchers concerned with violence in U.S. inner-cities have recommended preventative efforts such as the teaching of skills to resolve conflicts non-violently in the schools [111]. DuRant et al [100] recommend that for violence prevention, information alone will not be sufficient, as it has not in the battle against AIDS.…”
Section: Stage 4 Researchmentioning
confidence: 99%